A phylogenomic framework for assessing the global emergence and evolution of clonal complex 398 methicillin-resistant Staphylococcus aureus. Issue 1 (31st January 2017) - Gonçalves da Silva, Anders; Baines, Sarah L.; Carter, Glen P.; Heffernan, Helen; French, Nigel P.; Ren, Xiaoyun; Seemann, Torsten; Bulach, Dieter; Kwong, Jason; Stinear, Timothy P.; Howden, Benjamin P.; Williamson, Deborah A.
Abstract : Distinct clones of methicillin-resistant Staphylococcus aureus (MRSA) have emerged as important causes of infection in individuals who have exposure to livestock (livestock-associated MRSA; LA-MRSA). Clonal complex 398 (CC398) is the most prevalent LA-MRSA clone, and has been reported from several geographical settings, including Europe, the Americas and Asia. To understand the factors contributing to the global dissemination of this clone, we analysed CC398 MRSA isolates from New Zealand (NZ), a geographically isolated country with an economy strongly dependent on livestock farming. We supplemented the NZ CC398 MRSA collection with global datasets of CC398 MRSA and CC398 methicillin-susceptible S. aureus. Here, we demonstrate multiple sporadic incursions of CC398 MRSA into NZ, as well as recent importation and spread of a swine-associated clade related to the European LA-MRSA lineage. Within a larger global phylogenomic framework, Bayesian modelling suggested that this NZ clade emerged in the late 2000s, with a probable origin in swine from Western Europe. Elucidating the factors responsible for the incursion and spread of LA-MRSA in geographically distant regions, such as NZ, provides important insights into global pathways of S. aureus transmission, and will inform strategies to control importation and spread.